More food with less water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Deficit irrigation practices Water Reports No 22, FAO, 2002. 110 pp. ISBN 9251047685 US$ 17 Euro 15.75